Activities and Behavior of Cetaceans - Dwimei Ayudewandari Pranatami; Rini Devita Sari; Faza An'imah; Najwa Eka Roseva; Niken Rossiana Puspitasari; Nasywa Romadloniyah; Retno Cahyaningtyas (DIVERSITAS HAYATI, 2023)
The activities and behavior of several cetaceans show their own characteristics, from dolphins showing various movements to dugongs who like to hug humans. In this study we report and discuss scientific information about the various types of activities and characteristics possessed by animals belonging to the cetaceae. The research method is in the form of a literature review by searching for articles in the database, namely Google Scholar with the year 2003-2021. Articles are searched using keywords that have been determined by the researcher. Keywords for this search included the following terms: activity, behavior in cetaceae, locomotion in dolphins, whales, porpoises, sea lions, and seals. Based on the results of this literature review, we conclude that cetaceae are marine mammals that are quite unique, the activities of cetaceans are very diverse and the activities that are often shown are aerials